2009
DOI: 10.1007/s00334-009-0212-z
|View full text |Cite
|
Sign up to set email alerts
|

Carthamus species in the ancient Near East and south-eastern Europe: archaeobotanical evidence for their distribution and use as a source of oil

Abstract: We present an overview of archaeobotanical Carthamus spp. finds from Neolithic to medieval sites in the Near East and adjacent areas. A particular focus is put on the cultivated form of the genus. Safflower appears first in a number of early Bronze Age (3000 B.C.) sites in northern and central Syria. From there it apparently spread to Egypt, the Aegean and south-eastern Europe. The Near Eastern Bronze Age evidence shows a striking exclusiveness in the distribution patterns of safflower and flax, with flax bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Its use as an oilseed crop was considered to be relatively recent beginning from the first half of the twentieth century (Dajue and Mündel 1996). However, archaeo-botanical evidence suggests its cultivation as a major oil crop in the Near East dating back to the Bronze Age (Marinova and Riehl 2009). It has also been used as a platform for production of plant-derived pharmaceuticals (McPherson et al 2009;Flider 2013;Carlsson et al 2014), biofuels, and as a source of industrial oil (Velasco et al 2005;Ilkılıç et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Its use as an oilseed crop was considered to be relatively recent beginning from the first half of the twentieth century (Dajue and Mündel 1996). However, archaeo-botanical evidence suggests its cultivation as a major oil crop in the Near East dating back to the Bronze Age (Marinova and Riehl 2009). It has also been used as a platform for production of plant-derived pharmaceuticals (McPherson et al 2009;Flider 2013;Carlsson et al 2014), biofuels, and as a source of industrial oil (Velasco et al 2005;Ilkılıç et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that authors of reference 17 underestimated the global total number of Carthamus (25 instead of 37), and they concluded that this genus is not suitable as oil source, they actually contradict archeological evidences that this genus was used for oil production in the near east. 44 The use of this oil remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Safflower accessions from the Mediterranean region clustered together and revealed their genetic similarity, and possibly shared a similar parentage. Clustering of the safflower accessions from Mediterranean countries proposes this region as a center of safflower domestication, with Syria having a predominant role [8]. Population B clustered safflower accessions from the South Asian countries, i.e., Afghanistan, Iran and Bangladesh, but not Turkey.…”
Section: Genetic Structure and Diversity In Safflower Panelmentioning
confidence: 98%
“…Carthamus species have been utilized since the pre-historic period as its archeological remains were found at sites in Syria since 7500 BC. Safflower was distributed from its center of domestication (i.e., Syria) to linked regions comprising Egypt, the Aegean region and southern Europe [8].…”
Section: Introductionmentioning
confidence: 99%